2017
DOI: 10.4236/ojmh.2017.72004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Hydrology of a Data-Scarce Tropical Watershed Using the Soil and Water Assessment Tool: Case of the Little Ruaha River Watershed in Iringa, Tanzania

Abstract: The hydrology of the Little Ruaha River which is a major catchment of the Ihemi Cluster in the Southern Agricultural Growth Corridor of Tanzania (SA-GCOT) has been studied. The study focused on the hydrological assessment through analysis of the available data and developing a model that could be used for assessing impacts of environmental change. Pressures on land and water resources in the watershed are increasing mainly as a result of human activities, and understanding the hydrological regime is deemed nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…It was found that the runoff Soil Conservation Service runoff curve number (CN2) was the most sensitive parameter followed by Available Water Capacity of the Soil Layer (SOL_AWC), Threshold depth of water in the shallow aquifer required for return flow to occur (GWQWN), Groundwater Delay Time (GW_DELAY), Base Flow Alpha Factor (ALPHA_BF) and Soil Evaporation Compensation Factor (ESCO). These results are in agreement with the study reported by [11] that mentioned parameters are most sensitive to flow prediction. The most sensitive parameters were then considered for model calibration.…”
Section: Sensitive Parameterssupporting
confidence: 94%
“…It was found that the runoff Soil Conservation Service runoff curve number (CN2) was the most sensitive parameter followed by Available Water Capacity of the Soil Layer (SOL_AWC), Threshold depth of water in the shallow aquifer required for return flow to occur (GWQWN), Groundwater Delay Time (GW_DELAY), Base Flow Alpha Factor (ALPHA_BF) and Soil Evaporation Compensation Factor (ESCO). These results are in agreement with the study reported by [11] that mentioned parameters are most sensitive to flow prediction. The most sensitive parameters were then considered for model calibration.…”
Section: Sensitive Parameterssupporting
confidence: 94%
“…It is worth to note that the surface flow contributions of the Great Ruaha, Little Ruaha and Kisigo rivers to the total inflow to the Mtera reservoir are estimated as 56%, 18% and 26%, respectively (Kashaigili et al, 2005). Also, Mbungu and Kashaigili (2017) revealed reduction and changes of streamflows with time and therefore more water shortages are expected on the planned water development and related ecosystems in the Little Ruaha catchment. Moreover, Munkyala (2017) indicated that irrigation is the big water user in the Ndembera catchment, which accounts for about 77% of the all water demands in the catchment.…”
Section: Discussionmentioning
confidence: 97%
“…The average annual precipitation is around 685 mm (Hijmans et al 2005). The mean annual temperature in the scene ranges from 18°C at higher altitudes to 28°C (Mbungu and Kashaigili 2017). Elevation ranges from 698 m to over 2300 m (Mbungu and Kashaigili 2017).…”
Section: Methodsmentioning
confidence: 99%